If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -2x = x + -8 Combine like terms: 10x + -2x = 8x 8x = x + -8 Reorder the terms: 8x = -8 + x Solving 8x = -8 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 8x + -1x = -8 + x + -1x Combine like terms: 8x + -1x = 7x 7x = -8 + x + -1x Combine like terms: x + -1x = 0 7x = -8 + 0 7x = -8 Divide each side by '7'. x = -1.142857143 Simplifying x = -1.142857143
| 2/(3x^(4/3)) | | 4(2x-3)=1 | | 6=-3+a | | -11=v-7 | | 1+33.1x=4x-10 | | b-9=4 | | 4+b=12 | | 35.28/6.3 | | y=33.1x+1 | | 1x+.2x=246 | | 7/10-3/5= | | 2x-7=11-7 | | 6-2=2+z-2 | | 9(3)-2y=19 | | -5x-7x=x+7 | | y=6sin(4x+7) | | 7x-40=100 | | 20x^2=40x | | -4-5y=21 | | 2(x+1)-5(x+3)=2 | | z^8=-1+i | | 6.25-5X=24 | | 2=-132.4x+6 | | -8x-33=x | | y=-132.4x+6 | | 24x6y3/-6x3y | | cos(2x)+5cos(x)+3=0 | | -4x+3x=-8 | | c=31h+42 | | (14*-7)/5=7 | | 6=2+z | | -7(x-6)+6=48 |